2019
DOI: 10.1097/dcr.0000000000001230
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Colon Resections: Does Surgeon Specialization Influence Outcomes?

Abstract: BACKGROUND: Relationships between high-volume surgeons and improved postoperative outcomes have been well documented. Colorectal procedures are often performed by general surgeons, particularly in emergent settings, and may form a large component of their practice. The influence of subspecialized training on outcomes after emergent colon surgery, however, is not well described. OBJECTIVE: The purpose of this study was to determine whether subspecialty t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…Another propensity score-matched study showed that 88.9% of emergency laparoscopic colorectal colectomies were carried out by colorectal surgeons. 22 This observation aligns with several studies showing that colorectal surgery specialization is an independent factor for better outcomes in patients undergoing colorectal surgery. 23 This study showed that the laparoscopic approach in emergency settings is safe and feasible, with a trend towards better postoperative outcomes in line with growing evidence in the literature regarding the role of laparoscopy in emergency colorectal surgery.…”
Section: Results the Baseline Characteristic Distributions Presented Insupporting
confidence: 89%
“…Another propensity score-matched study showed that 88.9% of emergency laparoscopic colorectal colectomies were carried out by colorectal surgeons. 22 This observation aligns with several studies showing that colorectal surgery specialization is an independent factor for better outcomes in patients undergoing colorectal surgery. 23 This study showed that the laparoscopic approach in emergency settings is safe and feasible, with a trend towards better postoperative outcomes in line with growing evidence in the literature regarding the role of laparoscopy in emergency colorectal surgery.…”
Section: Results the Baseline Characteristic Distributions Presented Insupporting
confidence: 89%
“…The use of diverting ileostomy was more often used by colorectal teams, i.e., in 16.9% (54/319) compared to 5.7% (12/210) in the EST group and 8.7% (11/127) in the GST group, (p < 0.05). In turn, patients in the CRT group had higher rate of stoma reversal and of all patients alive after 3 years, 24 The number of examined lymph nodes was significantly less in the GST group compared with the other groups. Moreover, the rate of microscopically radical resection of the primary tumor did not differ between groups (Table 6).…”
Section: Secondary Endpointsmentioning
confidence: 84%
“…Operations performed by colorectal surgeons were associated with significantly lower rates of 30-day mortality (6.7% vs 16.4%, p = 0.001) and postoperative morbidity (45.0% vs 56.7%, p = 0.009). However, only 13.0% of the patients had a malignant disease [ 24 ]. A large population-based registry study from the UK showed that emergency laparotomy performed by consultants without a special interest in colorectal surgery had an increased adjusted 30-day mortality risk (OR 1.23, 95 CI 1.13–1.33) as well as increased risk of re-operation (OR 1.13, CI 1.05–1.20) compared to consultants with special colorectal interest [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency resection of the tumor with or without anastomosis remains the mainstay treatment for obstructive CRC -especially right-sided colon cancer, left-sided colonic obstruction that is not eligible for colonic stenting, and CRC with suspected bowel perforation [3]. However, postoperative morbidities and mortalities following surgical treatment for obstructive CRC are high [4] -even performed by colorectal surgeons [5].…”
Section: Introductionmentioning
confidence: 99%